Proposed solutions to citizen engagement in virtual environments of social participation: a systematic review. (30th April 2020) - Oliveira, Carlos
This paper aimed to understand how the engagement of citizens in virtual environments of social participation is studied in the literature. By virtual environment of social participation I understand: an Internet platform where themes for direct or indirect dialogue between civil society and the various spheres of government are made available through the digital participation of the citizen. A systematic review identified 96 papers, which were then analysed. Proposals to engage citizens in virtual environments of social participation use one of the following approaches: gamification, games, social networks, collaborative contribution or specific and personalised information. This study is important for researchers wanting to be current with the scientific state of the art. This review will also assist the scientific community working with citizen engagement in virtual environments of social participation to build a common understanding of the challenges that must be faced, and to identify areas where research is lacking.